Exploring the Financial Behavior of Micro, Small, and Medium Enterprises: Factors Influencing Financial Decision-Making - Alkaromi, Muhammad Amri; Cahyono, Dwi; Santoso, Budi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Micro, Small, and Medium Enterprises (known as UMKM, standing for Usaha Mikro, Kecil, dan Menengah) play a vital role in the national economy and in advancing the Sustainable Development Goals (SDGs), including poverty reduction (SDG 1), decent work and economic growth (SDG 8), and climate action through green economy initiatives (SDG 13). This study investigates the interaction of financial literacy, FinTech adoption, and local culture in shaping the financial decision-making of UMKM in Jember. Thematic analysis reveals that financial literacy supports strategic decision-making, FinTech enhances efficiency despite challenges of trust, and local culture influences financial practices. The sustainability of UMKM is shaped by innovation, community engagement, and SDG-oriented strategies. Recommendations include strengthening financial literacy training, promoting FinTech education, and integrating sociocultural aspects into business planning.